The Dynamics of Probiotics on Growth Performance and Immune Response in Broilers - Kabir, S.M.L.; Rahman, M.M.; Rahman, M.B.; Rahman, M.M.; Ahmed, S.U. (International Journal of Poultry Science, 2004)
The research work was conducted on "Hubbard Isa Starbro" broilers to evaluate the dynamics of probiotics relating to live weight gain, carcass yield, weight of cut up meat parts and immune response. Day old broiler chicks were divided into four groups as group A (Vaccinated probiotics fed group), B (Nonvaccinated probiotics fed group), C (Vaccinated conventional fed group) and D (Nonvaccinated conventional fed group). Groups C and D were taken as control birds fed with commercial ration and groups A and B as experimental birds were fed with commercial ration with the addition of 2gm probiotics (Protexin® Boost)/10 litres drinking water upto 6th week of age. The result evidenced the following information: (a) The live weight gains obtained were significantly (p